Studies on electrical & dielectric properties of rare-earth-based complex perovskite oxide Bi5Yb3O12 ceramic material synthesized via chemical route - Kumar A.; Kumar V.; kumar A.; Tiwary D.; Mandal K.D. (My University, 2025)
Bi5Yb3O12 (BYO) ceramic was synthesized utilizing a cost-effective chemical route method. XRD analysis as well as Le-Bail fitting was positively confirmed the single phase formation of BYO ceramic with cubic crystal system belonging to the space group of F m -3m. XPS analysis verified the correct oxidation states of various elements. Elemental composition was determined using EDS. The dielectric constant of BYO ceramic reached its peak at 337, measured at 382 K and 1 kHz. In contrast, its lowest recorded value was 238 at 523 K and 1 kHz. The tangent loss value of the BYO ceramic was noted as 0.2 at 293 K and 1 kHz, and 0.37 at 293 K and 1 MHz. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2024.